Prompt-to-Purchase : Leveraging Generative AI to Revolutionize E-Tail (Electronic – Retail) Customer Engagement - Giri, Arunangshu; Biswas, Wendrila (Indian Journal of Marketing, 2025)
Purpose : The study depicted the revolutionary approach of generative artificial intelligence (GAI) in e-tail that has boost customer engagement with tailored support, co-creation outcomes, predictive insights, and dynamic mapping of their shopping journey. The research identified crucial touch-points of the technology that resulted in intensified customer engagement and prompt-to-purchase action. Design/Methodology/Approach : An interview-based qualitative investigation was carried out utilizing NVIVO-15 software to develop a conceptual model using the extended technology acceptance model (TAM) model, customer engagement model, and stimulus-organism-response (S-O-R) theory. Thirty-seven semi-structured in-depth interviews with online customers were conducted using the convenience sampling technique. Findings : A conceptual model was developed to identify the factors impacting the prompt-to-purchase action of online customers. The study acknowledged directly and indirectly influencing factors (i.e., perceived usefulness, trust in GAI, perceived ease of use, -driven customer engagement, and purchase intention), which affected prompt-to-purchase action. Implications : The research delved deep into the fact that GAI in e-tail played a significant role in value creation for customers as well as the firm and stood as a game-changer. Its application in e-tail has not only provided creative assistance to its users but also augmented conversational commerce, driven product innovation, navigated through varied customer data patterns, and delivered customized service; it has eclipsed competitors and has hit the market ground well. Originality/Value : The study highlighted a holistic framework that provided a comprehensive view of the aspects of GAI and has driven greater effectiveness in customer engagement, which is rare and can serve as an optimistic model for commercial leaders in gaining advance momentum in business. The uniqueness of the model comprising the extended TAM Model, customer engagement model, and S-O-R theory provided a glaring aspect of leveraging AI to engross customers with e-tails.